2021
DOI: 10.1039/d1fo00727k
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between gut microbiota and flavonoid extract from Smilax glabra Roxb. and its potent alleviation of fatty liver

Abstract: Fatty liver is associated with intestinal microbiota dysbiosis and low-grade chronic inflammation. Herein, we report the interaction of flavonoids extract from Smilax Glabra Roxb. (FSGR) with gut microbiota, following the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…In contrast, FG with high molecular weight structure was more difficult to be fermented by Bacteroidetes, resulting in no significant change in the abundance of Bacteroidetes in the FG group. The ratio of Firmicutes to Bacteroidetes (F/B) increased in obesity, fatty liver, diabetes, hyperlipidemia, and other diseases (77)(78)(79)(80). Consistent with most studies, HFD increased the F/B value in this study.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, FG with high molecular weight structure was more difficult to be fermented by Bacteroidetes, resulting in no significant change in the abundance of Bacteroidetes in the FG group. The ratio of Firmicutes to Bacteroidetes (F/B) increased in obesity, fatty liver, diabetes, hyperlipidemia, and other diseases (77)(78)(79)(80). Consistent with most studies, HFD increased the F/B value in this study.…”
Section: Discussionsupporting
confidence: 91%
“…In the 16s rDNA sequencing analysis, an increase of Firmicutes/Bacteroidetes (F/B) ratio was found in the HFD group, which was also observed in ovariectomized mice with bone loss ( Wen et al., 2020 ; Xie et al., 2020 ) and people with primary osteoporosis ( Wang et al., 2017 ). Previous studies addressing obesity or nonalcoholic fatty liver disease have also demonstrated that HFD can induce an increase in F/B ratio ( Li et al., 2021 ), which is closely related to intestinal immune inflammation ( Zhao et al., 2021 ). In addition, HFD also led to a decrease in the abundance of SCFA-producing bacteria, such as Bacteroides , which exerts a bone protection effect via both promoting osteoblast differentiation ( Chen et al., 2007 ) and inhibiting osteoclast differentiation ( Lucas et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen components of SGR were detected by UHPLC-MS/MS, and eight compounds had good binding with ALDH2 through UHPLC-MS/MS and SYBYL 2.1.1. Traditional application of SGR can treat various diseases (such as inflammation, brucellosis, syphilis, and acute and chronic nephritis) and can also serve as an immune modulator and liver protector ( Wang et al, 2022 ; Zhao et al, 2021 ). Further molecular docking indicated that six compounds (cianidanol, phloretin, hesperetin, naringenin, naringin, and taxifolin 7-rhamnoside) may serve as potential intervention therapy drugs for hypertension protective factors.…”
Section: Discussionmentioning
confidence: 99%